Proceedings of the Proceedings of the Third Workshop on Multidisciplinary and Its Applications, WMA-3 2019, 11-14 December 2019 2020
DOI: 10.4108/eai.11-12-2019.2290862
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of SAW BORDA and TOPSIS BORDA Methods In the Zakat Recipient Determination System Education programs (Case Study: BAZNAS, West Kalimantan Province)

Abstract: The National Amil Zakat Agency (BAZNAS) is a zakat distribution institution that has many zakat distribution programs, one of which is in the field of Education. The process for zakat distribution program in the area of Education requires a support system for the Leadership Decision because of the determination of prospective recipients, namely the Head of the BAZNAS of West Kalimantan Province, the chairman of the registrant field, the chairman of the distribution division , the chairman of financial planning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Meanwhile, the interface testing to society showed a percentage of 87%. Sari et al [11] compared SAW BORDA analysis and TOPSIS BORDA analysis to determine the zakat recipient on Educational program. The findings revealed that both SAW BORDA analysis and BORDA analysis were biased to support the decision to decide the zakat recipient on the Educational program.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the interface testing to society showed a percentage of 87%. Sari et al [11] compared SAW BORDA analysis and TOPSIS BORDA analysis to determine the zakat recipient on Educational program. The findings revealed that both SAW BORDA analysis and BORDA analysis were biased to support the decision to decide the zakat recipient on the Educational program.…”
Section: Methodsmentioning
confidence: 99%